Evaluasi Pendapatan Asli Daerah berdasarkan Retribusi Pelayanan Sampah di Kota Tangerang - Asep Sugara (iLearning Journal Center, 2019)
The issue of waste in Indonesia is still a primary problem for regional governments, including the Tangerang City Government. In addition to the problem of waste management, another problem that arises is in determining the levy rates for garbage services in supporting waste services and management. The purpose of this study is to find several alternative formulations on the amount of fees for levies on waste services that are appropriate and applicable in Tangerang City through the results of academic studies and compare them with findings in the field. This study produced four formulations for determining the tariff for waste service fees, namely: 1) alternative one based on facts in the field using SNI 3242, 2) alternative two based on the use of population change coefficient, 3) alternative three based on the use of coefficient changes in the number of households and 4) alternative four based on the use of the population income hierarchy. These four formulations can be used as reference material for the Tangerang City Government to set a tariff for levies on garbage services in the future.